Distribution of eight organophosphorus pesticides and their oxides in surface water of the East China Sea based on high volume solid phase extraction method. (15th June 2021) - Xiao, Kaiyan; Zhu, Ningzheng; Lu, Zhibo; Zheng, Hongyuan; Cui, Chao; Gao, Yuan; Gao, Yunze; Meng, Xiangzhou; Liu, Yanguang; Cai, Minghong
Abstract: In this study, we reported the occurrence of eight organophosphorus pesticides (OPPs) in the East China Sea. Forty samples were collected and analysed with a high volume solid phase extraction method (Hi-throat/Hi-volume SPE) in the early summer of 2020. All the target OPPs were detected in the surface water at one or more stations in the East China Sea, and the concentrations of ΣOPPs were in the range 0.0775–3.09 ng/L (mean: 0.862 ± 0.624 ng/L). Terbufos sulfone and fenthion were the main pollutants in this area, probably resulting from pesticide use in China and other countries. The off-shore input from coastal regions was suggested to be a major source of OPP pollution in the East China Sea, and the movement of ocean currents played an important role in their transportation because around 0.86 t OPPs passed through the Tsushima Strait from the East China Sea each month. An ecological risk assessment showed that these OPPs presented a high risk to species in the East China Sea, whereas they posed no health risk to humans under both the median and high exposure scenario. Graphical abstract: Image 1 Highlights: Hi-throat/Hi-volume SPE was suitable for collecting and analyzing OPPs in seawater. The total concentration of eight OPPs was 0.0775–3.09 ng/L in the East China Sea. Around 0.86 t OPPs entered the Japan Sea from the East China Sea per month. There was a high ecological risk of OPPs to organisms in the East China Sea. Abstract : Hi-throat/Hi-volume SPE is effective in the collection and analysis of OPPs in seawater, and there is emerging risk of OPP exposure to organisms in the East China Sea.